Evaluation of Surface EMG in Masticatory, Sternomastoid, and Trapezius Muscles among Smartphone Users with Varying Duration of Mobile Usage: An Observational Cross-Sectional Study - Avinash E. Thakare; Pooja S. Salkar; Sandip M. Hulke; Santosh L. Wakode; Rajay N. Bharshankar; Anshul Rai (Advanced Biomedical Research)
Background: The overuse of smartphones can cause and trigger painful musculoskeletal conditions due to the derangement of muscle function. This study aimed to investigate the impact of daily smartphone usage on the surface electromyographic activity of the masticatory, sternomastoid, and trapezius muscles as there is limited research in this area. Materials and Methods: A total of 120 young adult smartphone users were categorized into three groups based on their daily duration of mobile usage. They underwent surface electromyography (sEMG) assessment using the Neuropack X1 surface EMG device from Nihon Kohden. Using appropriate statistical methods, the sEMG parameters were compared and correlated within the three groups. Results: The study found a significant increase in resting sEMG activity in the right Trapezius muscle among smartphone users who used their devices for more than 7 hours daily, compared to the other user groups (median interquartile range: 0.49 (0.026, 0.161) vs 0.025 (0.014, 0.049)). Furthermore, the maximum voluntary contraction testing revealed significantly higher sEMG activity in the right Temporalis muscle among smartphone users who used their devices for more than 7 hours daily, compared to the other user groups (median interquartile range: 2.342 (0.972, 3.364) vs 1.391 (0.525, 2.732) vs 1.301 (0.482, 2.083)). Conclusions: The findings suggest that the daily duration of smartphone usage could potentially impact the surface EMG activity of the masticatory, neck, and upper back muscles.